Comment on "Tribalism in American Politics: Are Partisans Guilty of Double Standards?" - Redding, Richard E. (Journal of Open Inquiry in the Behavioral Sciences, 2025)
This brief paper comments on the Bernstein et al. studies on "Tribalism in American Politics." Although the studies have some significant limitations, they provide a tantalizing window into the possibility that the state of affairs with respect to partisan bias may not be as sanguine as a recent meta-analysis suggests - that liberals and conservatives are equally biased against the other. On the contrary, until relatively recently, when researchers are now starting to challenge the received wisdom on the subject, the social and political psychology project has painted a relatively negative psychological portrait of conservatives and a positive one of liberals. By now, these portraits are well familiar to most psychologists and even much of the general public. Conservatives are more authoritarian, less intelligent, and more closed minded, among other things. Liberals are more enlightened, more flexible, and more open minded. But is this narrative correct? Could it be that liberals are more biased and less open-minded than conservatives, as the Bernstein et al. findings suggest, at least under some (perhaps even many) circumstances? The answer to this question, with its likely complexities, awaits further research.